Vinyl Records and Old Computers as Material Culture: Perspectives on Collecting and Donations to Museums - Van Der Grijp, Paul (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract This article aims to develop an anti-reductionist approach to two non-elite collecting realms: popular music and old computers. The article applies a configurational perspective by focusing on a set of psychological, sociological, economic, and educational collectors’ motives. These four motivational categories are operationalized in terms of ego-enlargement, augmentation of social status, speculation in view of profit, and acquiring and transmitting knowledge about the collectibles concerned. They may also be conceived as various forms of profit: psychological, sociological, economic, and educational profit. Music fans collect particular formats of music supports, genres, performers, record labels, producers, or combinations of these characteristics. The community of old-computer collectors consists of passionate, French-speaking collectors and users of original but obsolete computer material. The latter case study starts and ends with a conflict on the foundation of a museum on the history of computer technology.